Tuesday
March 28, 2017

Post a New Question

Posted by on .

13 - t = -t + 7
(13 - t) - 13 = (-t +7) -13
-t = -t - 6
-t + t = (-t - 6) + t
0 = -6

This makes no sense to me..
What is the answer to the problem
13 - t = -t + 7

  • Pre-Algebra - ,

    it cannot be solved, you did it right. These types of equations are called no solution.

  • Pre-Algebra - ,

    um.. whats the question??

  • Pre-Algebra - ,

    What is the answer to the problem
    13 - t = -t + 7

  • Pre-Algebra - ,

    -t = -t -6
    0=-6
    Thats the answer and you put no answer. That's just how some are.

  • Pre-Algebra - ,

    i was repeating the question; i'm not the op.

  • Pre-Algebra - ,

    Thank You all! I was trying to help my daughter and was all confused.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question